Reallocation and Technology: Evidence from the US Steel Industry - Collard-Wexler, Allan; De Loecker, Jan (American Economic Review, 2015)
We measure the impact of a drastic new technology for producing steel—the minimill—on industry-wide productivity in the US steel industry, using unique plant-level data between 1963 and 2002. The sharp increase in the industry's productivity is linked to this new technology through two distinct mechanisms: (i ) the mere displacement of the older technology (vertically integrated producers) was responsible for a third of the increase in the industry's productivity, and (ii ) increased competition, due the minimill expansion, drove a productivity resurgence at the surviving vertical integrated producers and, consequently, the productivity of the industry as a whole. (JEL D24, L13, L23, L61, M11, O31, O33)